Α-Linolenic acid-modified pluronic 127-CS copolymeric micelles for the skin targeted delivery of amphotericin B. (3rd December 2018) - Zhou, Feilong; Xu, Hongmei; Song, Zhimei; Zhu, Li; Feng, Sijia; Feng, Runliang
Abstract : In this study, an α-linolenic acid modified pluronic F127- block -chitosan (F127-(CS-LNA)2 ) copolymer was synthesized to prepare topical amphotericin B (AMB)-loaded micelles (AMB-M) via a dialysis technique. Abstract : In this study, an α-linolenic acid modified pluronic F127- block -chitosan (F127-(CS-LNA)2 ) copolymer was synthesized to prepare topical amphotericin B (AMB)-loaded micelles (AMB-M) via a dialysis technique. The drug encapsulation efficiency, particle size and zeta potential of AMB-M were 97.26 ± 2.85%, 140.00 ± 0.36 nm and 7.00 ± 0.54 mV, respectively. Characterization of AMB-M by Fourier transform infrared spectroscopy and powder X-ray diffraction revealed the presence of an interaction between AMB and the copolymer, and that AMB was present in AMB-M without any crystallization. AMB-M exhibited in vitro antifungal activity comparable to that of a commercial AMB injection (AMB-I), although it showed a slower AMB release than that of AMB-I. AMB-M showed a 310-fold increase in the drug skin deposition and better in vivo activity against a fungal infection of the skin as compared to commercial AMB liposomal gel, a topical formulation, which shows no AMB penetration through the skin. In addition, AMB-M showed inconspicuous skin irritation, and was stable at 4 °C for 30 days. In conclusion, F127-(CS-LNA)2 may be a promising and safe drug delivery vehicle for AMB in the treatment of topical skin fungal infections.